A portable device for real-time continuous drug monitoring in freely moving small animals - Tsyban, Yurii; Shetty, Saptami Suresh; Li, Yanyan; de Oliveira Filho, José Ilton; Merzaban, Jasmeen S.; Salama, Khaled Nabil (Biosensors & bioelectronics, 2025)
The large size and operational constraints of benchtop potentiostats, which typically require the use of anesthetized animals, have posed significant challenges for conducting real-time, long-term pharmacokinetic studies in freely moving subjects. This research addresses these challenges by developing a compact, portable electrochemical sensing platform capable of monitoring drug concentrations in real time within natural, dynamic environments. The system integrates lightweight, miniaturized electronics, and multiple electrochemical techniques with onboard data processing to eliminate the need for external computational support, while its energy-efficient design reduces reliance on large batteries. Experimental evaluations demonstrate that the device reliably measures drug concentrations using aptamer-based sensors and processes signals with baseline correction and drift compensation in situ. Unlike implantable systems, our externally mounted device offers the flexibility of quick attachment and replacement without surgical intervention, preserving animal welfare. These advancements open new avenues for pharmacokinetic research and closed-loop drug delivery systems by enabling continuous, high-frequency measurements in awake, freely moving small animals.